CONTROL OF HEAT TRANSFER AND FLUID FLOW VIA A MOVING FIN IN A TRIANGULAR ENCLOSURE FILLED WITH NANOFLUID - Kolsi, Lioua; Öztop, Hakan Fehmi; Al-Rashed, Abdullah A. A. A.; Aydi, Abdelkarim; Naceur, Borjini Mohamed; Abu-Hamdeh, Nidal (Begell House Inc, 2019)
A computational study has been pet formed to solve the heat transfer and fluid flow problem in a triangular enclosure filled with nanofluids. It also has a moving fin in its top side. Three different cases are considered: a fixed fin (V = 0), a fin rotating clockwise (V+), and a fin rotating counterclockwise (V-). The cavity is heated and cooled from inclined walls and bottom wall is adiabatic. Three-dimensional governing equations are solved by using the finite volume method. Other governing parameters are the Rayleigh number 10(3) <= Ra <= 10(6) and nanoparticle volume fraction 0.0 <= phi <= 0.15. It is found that heat transfer can be controlled via both a moving lid and particle addition into the base fluid.
Keywords: entropy generation; natural convection; moved fin; triangular enclosure; nanofluid